Mechanisms for Managing Innovation Activity in Enterprises: An Integrated Framework for Emerging Economies - Mahmudov Kahramon Saydullayevich; Gloria Oluchukwu Okeke (Research Parks Publishers, 2026)
Research objectives: This study investigates the mechanisms through which enterprises in transition economies, with particular focus on Uzbekistan, can effectively manage innovation activity. The primary objectives are to identify the key organizational, institutional, and technological drivers that facilitate or hinder innovation management; to assess the relative effectiveness of formal and informal innovation governance mechanisms; and to propose an integrated management framework tailored to the socioeconomic context of emerging economies. Design/Methodology/Approach: A mixed-methods research design was employed, combining a structured questionnaire survey administered to 148 enterprises across manufacturing, services, and technology sectors with semi-structured interviews conducted with 24 senior managers and innovation officers. Quantitative data were analyzed using weighted scoring models and descriptive statistical analysis, while qualitative findings were processed through thematic content analysis. Enterprises were stratified by size, ownership type, and industry sector to ensure representativeness. Research findings: Empirical results indicate that regulatory and bureaucratic barriers represent the most pervasive obstacle to innovation, particularly in state-owned enterprises (63%) and SMEs (71%). R&D investment intensity emerged as the highest-weighted criterion in the composite innovation management index, yielding a weighted score of 1.05 out of a possible 1.25. Cross-functional collaboration and external partnership intensity received the lowest composite scores, suggesting systemic weaknesses in collaborative innovation governance. Private enterprises demonstrated greater agility in technology adoption but faced more pronounced challenges in retaining qualified personnel. Theoretical contributions/Originality: This research contributes to the innovation management literature by proposing a six-dimensional Innovation Governance Index (IGI) specifically calibrated for transition economy contexts. Unlike existing frameworks developed primarily for advanced industrial economies, the IGI incorporates institutional readiness and regulatory environment as weighted variables, providing a more contextually valid measurement tool. Implications for practitioners/policy: Findings suggest that enterprise managers should prioritize formalizing innovation processes and investing in knowledge management infrastructure. Policymakers are advised to streamline regulatory procedures for innovation-active enterprises and incentivize cross-sectoral technology partnerships. The establishment of innovation hubs and technology transfer centers is particularly recommended. Limitations/Research implications: This study is constrained by its geographic focus on Uzbekistan and the cross-sectional nature of the survey, which limits causal inference. Future research should employ longitudinal panel data and extend comparative analysis to other Central Asian economies to validate and refine the proposed IGI framework.